CYCLONES AND ANTICYCLONES SOUTH OF 50 DEGREES SOUTH - NAVAL AIR STATION NORFOLK VA (1962)
Results of a study of the percentage frequency of occurrence of surface pressure systems on a monthly and seasonal basis are presented. Al though based upon the best available Southern Hemisphere surface synoptic charts, the results should be regarded as tentative due as much to the uncertainties of analysis over the tremendous expanse of the southern oceans and the continent of Antarctica as to the short period (6 years) for which surface charts were available. This study provides information in improving both the analysis and forecasting of meteorological events of importance to naval units operating south of 50 S.